The Ghost Story 1840-1920 : a cultural history. - Smith, Andrew, 1964- (Manchester University Press, 2010)
The Ghost Story 1840-1920: A Cultural History examines the British ghost story within the political contexts of the long nineteenth century. By relating the ghost story to economic, national, colonial and gendered contexts' it provides a critical re-evaluation of the period. The conjuring of a political discourse of spectrality during the nineteenth century enables a culturally sensitive reconsideration of the work of writers including Dickens, Collins, Charlotte Riddell, Vernon Lee, May Sinclair, Kipling, Le Fanu, Henry James and M.R. James. Additionally, a chapter on the interpretation of sp.
Keywords: Ghost stories, English -- History and criticism.; English fiction -- 19th century -- History and criticism.; English fiction -- 20th century -- History and criticism.; Literature and society -- Great Britain -- History -- 19th century.; Histoires de fantômes anglaises -- Histoire et critique.; Roman anglais -- 19e siècle -- Histoire et critique.; Roman anglais -- 20e siècle -- Histoire et critique.; Littérature et société -- Grande-Bretagne -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Gothic & Romance.; Literature.; English fiction; Ghost stories, English; Literature and society; Great Britain; 1800-1999; British ghost story.; Charlotte Riddell.; Henry James.; May Sinclair.; Vernon Lee.; long nineteenth century.; spectral language.; spectrality.; spirit messages.; textual analysis.; Criticism, interpretation, etc.; History